2022
DOI: 10.1002/bbb.2334
|View full text |Cite
|
Sign up to set email alerts
|

Biochar combined with nitrogen fertilizer: a practical approach for increasing the biomass digestibility and yield of rice and promoting food and energy security

Abstract: Rice is an important food crop that provides abundant biomass residues for biofuels. The use of nitrogen (N) fertilizer to increase rice biomass and yield in China has become increasingly common; however, the overuse of N fertilizer can create several environmental hazards and contribute to climate change. Biochar is well known for its ability to reduce N fertilizer amendment requirements without compromising rice yield and biomass. No studies to date have examined the effect of biochar on rice straw cellulose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…Nitrogen is often the most deficient of all the plant nutrients. Nitrogen is the key element in achieving consistently high yields in cereals (Iqbal et al, 2019;Iqbal et al, 2020, Ali et al, 2020Wu et al, 2021, Ali et al, 2022.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen is often the most deficient of all the plant nutrients. Nitrogen is the key element in achieving consistently high yields in cereals (Iqbal et al, 2019;Iqbal et al, 2020, Ali et al, 2020Wu et al, 2021, Ali et al, 2022.…”
Section: Introductionmentioning
confidence: 99%
“…Several alternative energy production technologies have been created, with crops biomass energy generation receiving particular attention due to its ecologically beneficial nature [ 1 , 2 ]. Rice is the most cultivated crop in Guangxi province of China and a staple food worldwide, resulting annually in more than 800 million metric tons of biomass [ 3 , 4 ]. However, a huge quantity of agricultural biomass is burned in the field and buried in soil in southern China, which is not environmentally friendly since it harms soil fauna and degrades soil quality.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, fertilizer management significantly affects rice biomass and its yield [ 5 , 6 , 7 ], and to improve rice yield and biomass, farmers excessively use chemical fertilizer, especially N, which is not eco-friendly [ 8 , 9 ]. To cope with this problem, many studies reported that biochar has the potential to decrease the requirement of N fertilizer without compromising rice yield and biomass [ 3 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations